Manajemen Diri (Self Management) Perilaku Sehat pada Pasien Hipertensi - Kurnia, Vera; Nataria, Desti (Jurnal Riset Hesti Medan, 2021)
Hypertension is one of the most common causes of morbidity and mortalityÂ  all over the world, also known as â€œthe silent killerâ€ because people with hypertension are without symptoms. West Sumatera Province reported that the prevalence of hypertension at the age 18 years has increased from 25,8% in 2013 to 31,7% in 2018. Successful strategies to manage the blood preasure depends on patients self-care management or the ability and willingness of the patient to change and maintain certain behavior.The purpose of this research is to determine the effect of self-education management of hypertension patients in the working area of primary health care in Bukittinggi.Design of this research is a quasi experimental design with pretest-posttest with control group. The sample which used were 62 respondents consist of 31 people in the intervention group and 31 people in the group control. Sampling was done by consecutive sampling technique. Data was analyzed Wilcoxon signed rank test and Mann Whitney test. The result of this research shows that there isnâ€™t any effect of self education management to healthy behavior which includes exercise and healthy diet of the intervention group and the control group at community health center in Bukittinggi (mean rank after the intervention < 10; p> 0,05). Based on the result of this research it can be concluded that the habits of respondents who carry out light and medium activities every day and also education provided by primary health careÂ  have given big impact to respondentâ€™s habits where they always do exercise and healthy diet in their daily life.The result of this research can be used as an input for primary health care to maintain and improve education of healthy behavior for hypertension patients.